Merchants’ Evaluation Of Critical Determinants Of Mobile Payment Services Adoption: A Scoping Review Of The Literature - Justino , Mateus Vicente; Mefi , Nteboheng Patricia (Journal of Ecohumanism, 2025)
As physical and electronic payment instruments are being integrated into mobile payment services, the uptake of the mobile payment service solutions by merchants and other market actors such as Big Tech, device manufacturers, financial institutions, consumer and regulators, has been increased. However, this paper highlights that despite considerable research on the adoption and use of mobile payment published in academic journals across disciplines, there has been little progress in the promotion of the adoption and use of mobile payment services by merchants. With the desire to strengthen the field, this study embarked on a scoping review of research to assess the progress of merchants’ evaluation of mobile payment services over 12 years. Seven online databases were searched, of which 53 articles were eligible for review. Results show that most studies were exploratory in nature, using a quantitative approach, rather than a mixed-method approach. Among the studies, 22 underpinning theories were found, of which the TOE framework, TAM and UTAUT2 were adopted in most of the studies. The study reported 66 critical determinants of the adoption of mobile payment solutions by merchants. In addition, the study has made recommendations and suggestions to help future research move in new and diversified directions.